2007
DOI: 10.1007/s12020-007-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of gonadotropin-releasing hormone on human ovarian epithelial cancer cell invasion

Abstract: Ovarian cancer is the most lethal of all gynecological cancers. Most deaths from ovarian cancer are due to widespread intraperitoneal metastases and malignant ascites. However, mechanisms of invasion in ovarian cancer remain poorly understood. In this study, we examined the effects of gonadotropin-releasing hormone (GnRH)-I (the classical mammalian GnRH), GnRH-II (a second form of GnRH), and GnRH receptor on invasion using two human ovarian carcinoma cell lines, OVCAR-3 and SKOV-3. Here we demonstrated that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…This difference in regulation suggests that high levels of GnRH receptor may enhance cellular response to GnRH stimulation, presumably because of more efficient signal amplification or altered signaling through coupling to different G proteins (Cheung and Wong, 2008). In support, we found that GnRH induces cell motility and invasive response selectively in Caov-3 and OVCAR-3, which express high levels of GnRH receptor (Cheung et al, 2006;Chen et al, 2007). In addition, GnRH has been shown to regulate its own synthesis, suggesting that GnRH may be involved in autocrine/ paracrine regulation (Kang et al, 2000).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This difference in regulation suggests that high levels of GnRH receptor may enhance cellular response to GnRH stimulation, presumably because of more efficient signal amplification or altered signaling through coupling to different G proteins (Cheung and Wong, 2008). In support, we found that GnRH induces cell motility and invasive response selectively in Caov-3 and OVCAR-3, which express high levels of GnRH receptor (Cheung et al, 2006;Chen et al, 2007). In addition, GnRH has been shown to regulate its own synthesis, suggesting that GnRH may be involved in autocrine/ paracrine regulation (Kang et al, 2000).…”
Section: Discussionsupporting
confidence: 70%
“…(c) Cells were grown on glass coverslips and immunostained with anti-p120 ctn antibody and then detected with Texas red-conjugated secondary antibody. stimulate cell migration/invasion, high concentrations inhibit these functions (Cheung et al, 2006;Chen et al, 2007). The reasons are unknown, but the receptor expression level is known to be a determinant of different signal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH isoforms and their synthetic relatives have been shown to have a dual action on GnRH receptor positive peripheral tissues (33). Low (nanomolar) concentrations of these peptides have exhibited a dose-dependent increase in cell proliferation, migration and invasion, yet concentrations over 100 nM have inhibited these functions (34). However, these actions may be inversed depending on the cell line and regardless of the tissue of origin.…”
Section: Effect On Tumour Cell Proliferationmentioning
confidence: 99%
“…However, these actions may be inversed depending on the cell line and regardless of the tissue of origin. In fact, it has been shown that GnRH can both induce and inhibit invasion of the human ovarian cancer cell lines, OVCAR-3 and SKOV-3, respectively (34). The mechanisms for these differences may be explained by the expression profiles of GnRH-R and their signal transduction.…”
Section: Effect On Tumour Cell Proliferationmentioning
confidence: 99%
“…GnRH receptor ligands have been shown to act differently on the GnRH receptor positive peripheral tissues at different doses (Mezo and Manea, 2010); a dose-dependent increase in cell proliferation at low (nanomolar) concentrations and inhibitory action at higher (micromolar) concentrations (Chen et al, 2007). This has been explained by the differential expression profiles of GnRH receptors (Mezo and Manea, 2010).…”
Section: Tumor Cell Proliferation Assay (Mtt Assay)mentioning
confidence: 99%